Evaluation of the Commission of the European Union's co-operation with the Caribbean region : final report - Burgaud, Jean-Marie, team leader (Commission of the European Union BrusselsBE, 2012)
Presents the findings of the 2011 Regional Level Evaluation. Aims to provide meaningful feedback to the Commission and the European External Action Service (EEAS), but also to the general public on the results achieved by the Commission's co-operation strategies and their implementation for the period 2003-2010 at regional level of the Caribbean region.